Social Media, Spirituality, and Consumerism: A Case Study of Marketing Spiritual Learning at SOUL - Anak Agung Gede Putra; Ida Bagus Gde Yudha Triguna; I Gusti Agung Paramita (PT. Global Research Collaboration, 2026)
This study examines the transformation of contemporary spirituality within a digital ecosystem shaped by consumer logic, using SOUL (Spirit of Universal Life) as the case study. Through the original analytical framework The Maker–The Market–The Meaning (3M), the research addresses how SOUL leverages social media to package and market spiritual learning; how commodification of meaning operates within SOUL's marketing ecosystem; and what implications these practices hold for audiences' spiritual subjectivity. A critical-interpretive qualitative approach combining digital ethnography (netnography) and Critical Discourse Analysis (CDA) was employed, with a critical paradigm as the epistemological meta-framework to manage researcher bias given the author's insider position as SOUL's CMO. Three key findings emerge: (1) The Maker builds digital spiritual authority through figural performativity, translation of teachings into social media formats, and self-technology tools (SOUL Meter and SOUL Care); (2) The Market reveals community evolution into spiritual prosumers unified by an